2020
DOI: 10.21203/rs.3.rs-117710/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cancer Associated Fibroblast-Derived IL-6 Determines Unfavorable Prognosis in Cholangiocarcinoma By Affecting Autophagy-Associated Chemoresponse

Abstract: Background: Interleukin-6 (IL-6) massively released by cancer-associated fibroblast (CAFs) has been shown to associate with the malignant behavior of cholangiocarcinoma (CCA). In vitro studies demonstrated the ability of CAFs-derived IL-6 to inhibit autophagy in CCA cells thus promoting their proliferation and invasiveness potential. Here, we aimed to validate with clinical and molecular data the hypothesis that CAFs infiltration and release of IL-6 predict poor prognosis in CCA patients following dysregulatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In cholangiocarcinoma, both in vitro and in vivo experiments show that CAF-derived IL-6 impairs the autophagy-associated apoptotic response to 5-FU in cancer cells. Cholangiocarcinoma patients with low stromal IL-6 levels and active autophagy flux in the cancer cells have a better prognosis and more effective response to postoperative chemotherapy [67].…”
Section: Caf and Cell Survivalmentioning
confidence: 99%
“…In cholangiocarcinoma, both in vitro and in vivo experiments show that CAF-derived IL-6 impairs the autophagy-associated apoptotic response to 5-FU in cancer cells. Cholangiocarcinoma patients with low stromal IL-6 levels and active autophagy flux in the cancer cells have a better prognosis and more effective response to postoperative chemotherapy [67].…”
Section: Caf and Cell Survivalmentioning
confidence: 99%
“…The previous study has demonstrated that IL-6 secreted by CAFs could inhibit autophagy in CCA cells to stimulate CCA progression [145]. Moreover, IL-6 released by CAFs could educate neighboring CCA cells, rendering them less sensitive to chemotherapeutics via inhibiting the autophagy stress-response to the drug [146]. MiR-206 acted as a suppressor factor in liver cancer and played a suppressive role in the activation of HSCs, the crosstalk of CAFs with CCA cells reduced MiR-206 expression, which induced the conversion of NFs into CAFs and enhanced their secretion of IL6.…”
Section: Cafs Enhance Chemoresistance Of Cca Cellsmentioning
confidence: 99%
“…Contrastingly, a defective autophagic phenomenon may produce a p62 upregulation in human tumors (17,18). Some reports have documented an evident p62 expression in pancreatic, hepatocellular, mammary, and oral squamous carcinomas, in which aggressive clinicopathological features and poor prognosis have been referred (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%